2016
DOI: 10.1161/cir.0000000000000444
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Duration and Quality: Impact on Lifestyle Behaviors and Cardiometabolic Health: A Scientific Statement From the American Heart Association

Abstract: Sleep is increasingly recognized as an important lifestyle contributor to health. However, this has not always been the case, and an increasing number of Americans choose to curtail sleep in favor of other social, leisure, or work-related activities. This has resulted in a decline in average sleep duration over time. Sleep duration, mostly short sleep, and sleep disorders have emerged as being related to adverse cardiometabolic risk, including obesity, hypertension, type 2 diabetes mellitus, and cardiovascular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
520
1
14

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 714 publications
(586 citation statements)
references
References 193 publications
16
520
1
14
Order By: Relevance
“…St‐Onge et al recently published a scientific statement on behalf of the American Heart Association 91. Their review surveyed the literature and found that sleep duration, mostly short sleep, and sleep disorders are related to adverse cardiometabolic risk, such as obesity, hypertension, type 2 diabetes mellitus, and CVD.…”
Section: Discussionmentioning
confidence: 99%
“…St‐Onge et al recently published a scientific statement on behalf of the American Heart Association 91. Their review surveyed the literature and found that sleep duration, mostly short sleep, and sleep disorders are related to adverse cardiometabolic risk, such as obesity, hypertension, type 2 diabetes mellitus, and CVD.…”
Section: Discussionmentioning
confidence: 99%
“…Women are more prone than men to depression, which is linked to insomnia 10. While the adverse effects of severe sleep disturbances, such as obstructive sleep apnea (OSA) and insufficient sleep, on metabolic and vascular health have recently been recognized in both men and women,11, 12, 13, 14 the effects of highly prevalent, milder sleep disturbances, such as perceived poor sleep quality and insomnia on vascular health, are not well characterized in women, a population particularly vulnerable to these conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The impact of sleep disorders on cardiovascular disease (CVD) and metabolic disorders is impressive. Recent epidemiological studies reinforce this association between sleep deprivation and the increase in the incidence of hypertension, obesity, coronary diseases, diabetes and dyslipidemia (1) . The presence of obstructive sleep apnea hypopnea syndrome (OSAHS) or insomnia significantly increase the risk of CVD (arrhythmias, atherosclerosis, coronary heart disease, heart failure, hypertension and stroke) and metabolic disorders (overweight, type 2 diabetes mellitus and dyslipidemia) (6)(7)(8) .…”
Section: Introductionmentioning
confidence: 86%
“…The increase in the rates of sleep disorders (SD) and its negative effects on cardiovascular disease has been raising interest in researchers from all over the world (1) . According to the American institute National Heart, Lung, and Blood Institute approximately 50 to 70 million adults suffer from sleep disturbance or report poor habitual sleep (2) .…”
Section: Introductionmentioning
confidence: 99%